2010
DOI: 10.1152/ajprenal.00352.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-VEGF signaling pathway acts as a key modulator of vascular, lymphatic, and inflammatory cell responses of the bladder to intravesical BCG treatment

Abstract: -neutralizing antibodies and then were challenged chronically with intravesical PBS or BCG. At the end of chronic challenge period, a fluorescent internalizable tracer, scVEGF/Cy5.5, was administered to all mice and near-infrared fluorescence images were obtained in vivo and in real time. BCG increased the overall accumulation of scVEGF/Cy5.5 in the urinary bladder urothelium and inflammatory cells. In addition, BCG increased the density of blood and lymphatic vessels concomitantly with an upregulation of NRP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical instillation of VEGF produced bladder inflammation, increased voiding frequency, increased abdominal sensitivity and increased bladder nerve density in specific nerve populations including TRPV1-, substance P-, and calcitonin gene-related peptide-immunoreactive nerve fibers (Malykhina et al, 2012; Saban et al, 2011). Other roles for VEGF-VEGF receptor system in the lower urinary tract may involve inflammation-induced lymphangiogenesis and angiogenesis (Saban et al, 2010; Saban, 2015). The present studies demonstrating increased VEGF transcript expression in the urothelium and detrusor of WT and NGF-OE mice with CYP-induced cystitis are consistent with previous studies demonstrating contributions from the VEGF-VEGF receptor system in the structure and function of the lower urinary tract (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…During estrus, mRNA levels were highest for members of the angiopoietin system (angiopoietin 2, ANGPT2; angiopoietin-like 1, 2, and 4, ANGPTL1, ANGPTL2, and ANGPTL4, respectively; TEK tyrosine kinase, TEK), the VEGF system (a coreceptor for VEGF, neuropilin 2, NRP2; vascular endothelial growth factor A, VEGFA; kinase insert domain receptor, KDR, also known as fetal liver kinase-1 [FLK1] or vascular endothelial growth factor receptor 2 [VEGFR2], genes related to endothelial cell regulation (endothelins 1 and 2, EDN1 and EDN2; the receptor for EDN1, endothelin receptor type A, EDNRA; endothelial cell surface expressed chemotaxis and apoptosis regulator, ECSCR), angiotensin I-converting enzyme (peptidyl-dipeptidase A) 2 (ACE2), renin (REN), and FGF2. Although a study of vascular density in the equine endometrium did not reveal significant differences between the follicular and the luteal phase [50], the up-regulation of these genes are signs of vascular changes, which could be related to the observation that ''inflammatory response'' genes are overrepresented during estrus, because inflammatory responses and vascular responses are tightly connected [51]. Furthermore, up-regulation of a number of angiogenic factors by E2 has been shown in sheep [52].…”
Section: Genes Related To Angiogenesis Vasculature Development and mentioning
confidence: 92%
“…[21][22][23] Based on data obtained in a previous observational clinical study in bladder cancer patients receiving intravesical BCG therapy as well as published experimental data, we concluded that multiple BCG treatments resulted in a "prime/boost" response for the innate immune system. 21,24,25 Intermittent intravesical therapy resulted in tissue remodeling with increased vascularization, thus accounting for a 200-fold increase in neutrophils influx, a 120-fold increase in inflammatory monocytes and a 30-fold increase in natural killer cells. 21 Using quantitative data from this study as well as our knowledge of the kinetics of bladder tumor growth, we reasoned that it would be possible to establish a mathematical model that could help test the prediction that the innate immune response accounts for the success of bladder cancer immunotherapy.…”
Section: Resultsmentioning
confidence: 99%